Strategic Leadership Roles of Hospital Leaders on Delivering High-Quality Sickle Cell Disease and Hemophilia Care in Kenya - Mbunya, Samuel (Digital Repository of Theses, 2024)
Background Challenges have been identified in the Kenyan healthcare system, especially on the service delivery of care in general and specifically to the people living with Sickle Cell Disease and Hemophilia. This study determines the strategic roles of hospitals leadership toward delivering high-quality sickle cell disease and hemophilia care, by determining the effect of strategic leadership practices and to developing an effective strategic leadership model in the provision of high-quality sickle cell disease and hemophilia care in Kenya. Methods The study targeted 558 hospitals that of public, private, and faith-based hospitals registered and categorized as level 4, level 5 and level 6. The study stratified the sampled 233 hospitals into 3 levels of hospitals (4, 5 and 6). Purposive sampling from the non-probability sampling technique was used to purposively pick 3 management officials (Head of department, supervisors and one medical staff and one client (sickle cell disease and hemophilia patients) seeking care from the hospital), giving a total sample of 928 respondents. This study used both closed-ended and open-ended data collection instruments. Pilot’s study was conducted to identify any likely faults in the research tool by evaluating its validity and reliability. Face validity was attained when the questionnaire was critiqued by supervisors and experts and necessary adjustments done. Further, to accomplish construct validity, convergent and discriminant validity was tested using factor analysis. To check the reliability of the survey instrument, the study used Cronbach’s Alpha. Data was analyzed using descriptive statistics and structural equation modeling with aid of Analysis of Moment of Structure (AMOS 21) in SPSS version 26. Results The study underscores the substantial influence of strategic leadership on the provision of High-Quality Sickle Cell Disease and Hemophilia Care, revealing a clear positive correlation between strategic leadership and service delivery. Notable strengths observed include a dedicated focus on employee training and the adeptness in adapting organizational structures to leverage emerging opportunities. Additionally, moderately practiced aspects encompass the ability to adjust plans in response to evolving circumstances, implement disciplinary measures for communication gaps, and foster collaboration among departments. However, shortcomings in ensuring employee comprehension of institutional priorities and evaluating performance were identified as areas in need of improvement. Discussion and Conclusion In conclusion, the study emphasizes the pivotal role of strategic leadership in optimizing healthcare services for High-Quality Sickle Cell Disease and Hemophilia Care, urging targeted efforts to tackle identified challenges. Therefore, it recommends bolstering existing strengths, particularly through enhanced employee training and communication strategies, while advocating for continual refinement of strategic leadership practices to elevate the delivery standards for such specialized care.